Prognostic Biomarker SLCO4A1 Is Correlated with Tumor Immune Infiltration in Colon Adenocarcinoma - Xiaolong Chen; Gangfeng Yi; Yu Zhou; Weijun Hu; Lingyun Xi; Weilan Han; Fei Wang (Hindawi Limited, 2023)
Background. Solute carrier organic anion transporter family member 4A1 (SLCO4A1), a member of solute carrier organic anion family, is a key gene regulating bile metabolism, organic anion transport, and ABC transport. However, the association of SLCO4A1 with prognosis and tumor immune infiltration in colon adenocarcinoma (COAD) remains indistinct. Methods. Firstly, we explored the expression level of SLCO4A1 in COAD via GEPIA, Oncomine, and UALCAN databases. Secondly, we used the Kaplan-Meier plotter and PrognoScan databases to investigate the effect of SLCO4A1 on prognosis in COAD patients. In addition, the correlation between SLCO4A1 and tumor immune infiltration was studied by using TIMER and TISIDB databases. Results. Our results showed that SLCO4A1 was overexpressed in COAD tissues. At the same time, our study showed that high expression of SLCO4A1 was associated with poor overall survival, disease-free survival, and disease-specific survival in COAD patients. The expression level of SLCO4A1 was negatively linked to the infiltrating levels of B cells, CD8+ T cells, and dendritic cells in COAD. Moreover, the expression of SLCO4A1 was significantly correlated with numerous immune markers in COAD. Conclusions. These results indicated that SLCO4A1 could be associated with the prognosis of COAD patients and the levels of tumor immune infiltration. Our study suggested that SLCO4A1 could be a valuable biomarker for evaluating prognosis and tumor immune infiltration in COAD patients.